Generation of rotational flow for formation of spheroids by using microfluidic and dielectrophoretic hybrid device. (2016) - Kojima, Masaru; Horade, Mitsuhiro; Takai, Hirochika; Ohara, Kenichi; Tanikawa, Tamio; Kamiyama, Kazuto; Mae, Yasushi; Arai, Tatsuo
Toroidal-like sheroids are important in the field of tissue engineering. However, the formation processes of toroidal-like spheroids may not be considered efficient, as most of them are manual. In this paper, we suggest the possibility and effectiveness of applying microfluidics for formation of toroidal-like spheroids. The concept of our method is that cells are compressed by rotational flow in a microchannel and dielectrophoretic force. Some types of microchannels that can generate rotational flow were designed and were analysed with flow analysis software. A superior microchannel was fabricated, and a flow of NIH3T3 cell suspension was supplied to the channel. As the flow rate was changed, the cells were rotated in the microchannel according to our concept, and approximately 30% of them remained in the channel. This result supports our concept: toroidal-like spheroids can be formed under the influence of forces of rotational flow and dielectrophoresis.